Hyperembodiment a jewellery creation hub + community for women - Dewar, Katherine Jane (My University, 2016)
Hyperembodiment is an approach to negotiating the interface between spaces for women (in Johannesburg’s inner-city) and jewellery as a connector of the body – especially for women – to place. The inner-city, a space that is male-dominated and where women are present but seem to be largely excluded, or to feel unsafe and vulnerable - especially because of what the female body represents in an ‘unsafe’ male space, is also full of vibrancy and activity and has the potential for a positive and radical cultural change, but remains disconnected, nonprogressive and stagnant in thinking as well as non-inclusive of all people. The spatial investigations into places for women (modern feminist spatial concepts) and jewellery as a ‘site’ or interface between the body and architecture, and the interesting parallels it draws between feminist views, space, psychology and the body (process and development of body adornment and jewellery theories), are powerful ways of thinking about space that could suggest an appropriate architectural approach that could realign both spaces for women, a modern approach to the act of making, and creative jewellery practices in Johannesburg. The spatial connotations of the word ‘hyper’ is something that is ‘very’, ‘beyond’, or ‘very active’ and those of the word ‘embodiment’ is something ‘embodying’, ‘representing’ or ‘expressing’ a space. The compound word ‘Hyperembodiment’ used here means beyond embodiment, or very actively personifying a space and its innate properties of land, earth, materials, and the bodies (people) in it. It is also all the layers of embodiment – physical, historical, social layers – that are collaged together in one time and in one space to create a high-intensity and complex expression of place. Jewellery as a connector; for the body and for woman to place, would be these collaged layers made into a physical object and symbol made from the materials, earth, historical and social layers. It is a simultaneous case of the wearer embodying the place, and the place embodying the wearer.
Thesis is submitted in partial fulfilment for the degree: Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2016
Keywords: Public spaces--South Africa--Johannesburg; Community development--South Africa--Johannesburg; Feminism--South Africa; Women--South Africa--Social conditions